Development of Visual Literacy Assessment Instrument for Elementary School Students - Kurniawati, Kurniawati; Wahyuriningsih, Isnaini; Stotlikova, Rima (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
The development of visual literacy skills has become increasingly important in the digital age, especially for elementary school students who are constantly exposed to various forms of visual media. However, there is a lack of validated assessment tools specifically designed to measure visual literacy abilities among elementary students. This study aimed to develop and validate a comprehensive visual literacy assessment tool for fifth-grade students. The development process followed a systematic approach, including a literature review, expert validation, pilot testing, and psychometric analysis. The research involved 200 fifth-grade students from Jatiyoso District, Karanganyar Regency. Content validity was established through expert review, while construct validity was examined using Exploratory Factor Analysis (EFA). The instrument demonstrated excellent internal consistency with a Cronbach's alpha of 0.930 and strong test-retest reliability. The final tool consists of 10 items distributed across four domains: reading visual objects, understanding meanings from visual objects, evaluating visual objects, and creating visual objects. Factor analysis revealed a four-factor solution explaining significant variance in visual literacy skills. The tool provides educators and researchers with a reliable means for assessing visual literacy skills and can inform instructional decisions in elementary education. This study advances the field by offering a validated measurement instrument that fills the gap in visual literacy assessment for young learners.